Dynamism of Availability and use of Textbooks: A Hermeneutic Phenomenological Study of School Education in Nepal - Rupendra Joshi; Megh Raj Dangal (Universitas Riau, 2020)
The main aim of this research paper is to explore the dynamism of availability and use of textbooks in school education of Nepal and giving recognition to pedagogical attributes and quality assurance competencies. Textbooks are reliable and trusted supporting materials that provide deeper understanding of critical concepts on the subject matter. The hermeneutic discussion with five secondary teachers and twenty students from community school of Nepal reports the necessity and glory of textbooks in the daily practices in the classrooms which ultimately equipped for knowledge economy and enhancing skill development for the sustainable growth of the nation. The availability of textbooks provides a mental framework for teachers and students on what and how to teach students and what to learn in the classroom. The research was conducted with the purposive sample with 25 participants of community school from urban and rural area of Nepal. The findings of the research made clear that the availability and use of textbooks are not same and the government of Nepal must allocate sufficient budget to provide textbooks to the school going students so that availability and use of textbooks will be creatively enhanced and also develop the culture of using textbooks and sharing with their friends in the classrooms shaping their future and academic success.